Correlation of Character Values in the Qur'an and Hadith in Hamziyah Ahmad Syauqi Poetry Towards the Ethics of PBA College Students at UIN Walisongo - Iqbal Ahsanul Aula; Fiki Roi’atuz Zibrija; Nazih Sadatul Kahfi (Journal on Education, 2024)
This study aims to determine the correlation of character values in the Qur'an and hadith in Hamziyah Ahmad Syauqi on the ethics of PBA UIN Walisongo College Students. The approach used to obtain data is a mix method through the technique of distributing questionnaires, observations and interviews. with the pattern "the dominant-less dominat design", Population of PBA College Students of UIN Walisongo Semarang. The samples used in this study were 50 PBA UIN Walisongo College Students, 3 lecturers and 10 College Students to conduct interviews. The data collection technique used in this needs analysis is a survey technique. The questionnaire was used as a tool that was compiled and distributed through the Google form platform. The data analysis used is descriptive statistical analysis. Based on the validity and reliability test results, it can be determined that the questionnaire used for data collection has valid and reliable items. According to the survey results, 97% of the character values contained in Hamziyah ahmad syauqi affect College Students' ethics.